Hypertension and maternal urinary tract infection and the metabolic conditions of preterm infants - Talita Bavaresco; Rafael Andrade Menolli; Bruna Juliana Zancanaro Frizon; Claudia Silveira Viera; Julia Reis Conterno; Ana Tereza Bittencourt Guimarães; Sabrina Grassiolli
ABSTRACT Objective: The present study evaluated the anthropometric and metabolic profiles of preterm infants (PT) born from mothers with urinary tract infections (UTI) and mothers with hypertensive disorders (HD). Method: This was a longitudinal prospective study conducted between May 2015 and August 2016. First, 59 mothers with premature birth were included; after excluding 29 mothers, two subgroups were created: UTI-mothers (n=12) and HD-mothers (n=18). The anthropometric and metabolic variables of mothers and their respective PT were analyzed at birth and at 6 months of corrected age (CA). Results: Plasma triglyceride levels were higher among HD-mothers and their respective PT in comparison with UTI-mothers and their PT at 6 m of CA. Conclusion: Plasma triglyceride level is an important metabolic biomarker in HD-mothers resulting in higher triglyceride levels among PT at the CA of 6 m, suggesting an early programming effect of maternal hypertension.